ANALISIS PERANAN ACTIVITY BASED COSTING SYSTEM PADA PT. TIRTA MAHAKAM RESOURCES TBK. DI SAMARINDA - Umar Hi Salim (LPPM University 17 Agustus 1945 Samarinda, 2019)
The purpose of this paper is to find out the magnitude of the results of the imposition of Factory Overhead Costs on each product by implementing the Activity Based Costing System. The calculation results show that the difference in the burden of factory overhead using the traditional management accounting system with Activity Based Costing System shows that there are differences in each product, Plywood, Sawmill and Fancywood absorb factory overhead costs with traditional management accounting systems lower than Activity Based methods. Costing System (ABC) with costs of Rp. 5,056,946,700, -, Rp. 955,958,600 and Rp. 1,311,464,900 respectively, while Blockboard and Coating products absorb factory overhead costs using the Activity Based Costing System (ABC) method more. lower than the traditional management accounting system method with costs of Rp. 4,994,382,200 and Rp. 2,315,936,800The results of the per M3 cost calculation using the traditional management accounting system with Activity Based Costing System for each type of product produced by PT. Tirta Mahakam Resources Tbk. For Plywood, Sawmill and Fancywood products the difference in cost of goods with traditional accounting systems is lower than the activitybased costing system, while Blockboard products and coatings have a difference in the cost of products with an Activity Based Costing System lower than traditional accounting systems. The results of the calculation of product cost of the five products with the imposition of factory overhead costs using Activity Based Costing System illustrate the pattern of consumption of factory overhead costs which better reflects the amount of costs absorbed by each product. This is due to the fact that the Activity Based Costing System has a more cost center, so that the use of resources can be followed carefully to the cost center that consumes it. Thus, it can be seen that the Activity Based Costing System results in the loading of factory overhead costs which better reflect the amount of costs absorbed by each product than the traditional management accounting system.